2017
DOI: 10.1097/hjh.0000000000001131
|View full text |Cite
|
Sign up to set email alerts
|

The antihypertensive MTHFR gene polymorphism rs17367504-G is a possible novel protective locus for preeclampsia

Abstract: Objective:Preeclampsia is a complex heterogeneous disease commonly defined by new-onset hypertension and proteinuria in pregnancy. Women experiencing preeclampsia have increased risk for cardiovascular diseases (CVD) later in life. Preeclampsia and CVD share risk factors and pathophysiologic mechanisms, including dysregulated inflammation and raised blood pressure. Despite commonalities, little is known about the contribution of shared genes (pleiotropy) to these diseases. This study aimed to investigate wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 59 publications
0
7
0
1
Order By: Relevance
“…It is thus not surprising that our results differ from previous BP trait GWAS with UK Biobank. Still, even with all the caveats, a large number of the loci, notably CACNB2, MTHFR, and PLCD3, have been reported to be linked to hypertension in previous studies (Levy et al, ; Newton‐Cheh et al, ; Thomsen et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…It is thus not surprising that our results differ from previous BP trait GWAS with UK Biobank. Still, even with all the caveats, a large number of the loci, notably CACNB2, MTHFR, and PLCD3, have been reported to be linked to hypertension in previous studies (Levy et al, ; Newton‐Cheh et al, ; Thomsen et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…Ген MTHFR кодирует аминокислотную последовательность фермента, играющего ключевую роль в метаболизме фолиевой кислоты, который преобразует 5,10-метилентетрагидрофолат в 5-метилтетрагидрофолат, активную форму фолатов, и участвует в превращении гомоцистеина в метионин. Плейотропное влияние гена MTHFR описано более чем в 2 900 научных публикациях, полиморфизмы ассоциируются с сердечно-сосудистыми заболеваниями (ССЗ), ишемическими инсультами, болезнью Паркинсона, дефектами развития нервной трубки плода, онкологическими заболеваниями, осложнениями беременности и офтальмологической патологией (глаукома, катаракта, диабетическая ретинопатия) [1][2][3]. Одним из наиболее изученных полиморфизмов гена MTHFR, влияющим на активность фермента, является вариант, в котором нуклеотид цитозин (C) в позиции 677 заменен тимином (T).…”
Section: Discussionunclassified
“…At the same time, we also found that the G mutation of MTHFR rs17367504 had had a protective effect on Hcy during pregnancy, and the G mutation might cause Hcy decline. This might explain Thomsen's ndings [12]. Thomsen [12] rst found that the G mutation at MTHFR rs17367504 was a protective factor for PE (OR=0.65, 95% CI 0.53-0.80).…”
Section: Changes In Hcymentioning
confidence: 97%
“…This might explain Thomsen's ndings [12]. Thomsen [12] rst found that the G mutation at MTHFR rs17367504 was a protective factor for PE (OR=0.65, 95% CI 0.53-0.80). In addition to the MTHFR gene, creatinine and protein levels in pregnancy were also possible factors that in uence Hcy in pregnancy.…”
Section: Changes In Hcymentioning
confidence: 97%